The effectiveness of blended learning of “substance” unit in the science curriculum in terms of developing achievement and skills of scientific thinking in primary school students - Al-Qarni, Saad bin Abdullah (Arab Journal for Sciences and Research Publishing, 2017)
This research aims to determine the effectiveness of blended learning of “substance” unit in the science curriculum in terms of developing achievement and skills of scientific thinking in fifth grade students. The researcher used the two methods; Descriptive: to collect the necessary and semi-experimental metadata, the tool was an achievement test. And a scale of scientific thinking skills for the fifth grade curriculum. Both tools were applied to a sample of 63 students in the fifth grade, divided into two groups: experimental group 32 students, and control group 31 female students. After the processing of the statistical data, the following results were shown: Five basic skills of scientific thinking were identified, which can be developed in the unit of “substance” in the science curriculum which are: feeling the problem and defining it, setting hypotheses, testing hypotheses, interpretation and generalization. The unit was prepared using blended learning strategy for the fifth grade for the year 1435/1436 AH, and validity of the guide was checked. There are also statistically significant differences at the level of significance (α 0.05 0.05) between the mean scores of the students of the two groups; experimental and control in the post-application of the scale of scientific thinking skills in favor of the experimental group. Also, there are significant differences between the average scores of the experimental group in the two post- In the skills of scientific thinking for the benefit of the post-application, and found a positive correlative relationship function; (0.81); between the level of achievement of students and their level of scientific thinking in the post-application. In the light of the results of the research, the researcher recommends experimenting teaching the unit of “substance” using blended learning strategy with other samples of the students of the fifth grade, and preparing various teaching units of science curricula in different classes in the light of blended learning and providing internet access for teachers. As well as training teachers of science in the primary stage on using blended teaching, and the use of the scale of scientific thinking skills, and finally; studying school environment at various educational stages with appropriate tools and methods to teach science curricula in the light of blended learning.